2011
DOI: 10.4061/2011/395357
|View full text |Cite
|
Sign up to set email alerts
|

Fall Prevention Knowledge, Attitude, and Practices of Community Stakeholders and Older Adults

Abstract: We assessed knowledge, attitude, and provision of recommended fall prevention (FP) practices by employees of senior-serving organization and participation in FP practices by at-risk elders. The Washington State Department of Health administered structured telephone surveys to 50 employees and 101 elders in Washington State. Only 38% of employees felt “very knowledgeable” about FP, and a majority of their organizations did not regularly offer FP services. Almost half (48%) of seniors sustained a fall within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 22 publications
11
37
0
1
Order By: Relevance
“…This is in contrast to the data generated in the context of rigid trial circumstances (8, 17, 18) wherein healthy volunteer bias may result in levels of adherence (i.e., follow-through on referrals) that are unlikely to be achieved under real-world conditions. We and others have previously documented low engagement in fall prevention activities (19, 20), and so the importance of such real-world data cannot be underestimated.…”
Section: Discussionmentioning
confidence: 88%
“…This is in contrast to the data generated in the context of rigid trial circumstances (8, 17, 18) wherein healthy volunteer bias may result in levels of adherence (i.e., follow-through on referrals) that are unlikely to be achieved under real-world conditions. We and others have previously documented low engagement in fall prevention activities (19, 20), and so the importance of such real-world data cannot be underestimated.…”
Section: Discussionmentioning
confidence: 88%
“…Although community service providers may wish to sponsor fall prevention programs, they often do not have adequate knowledge of best practices in fall prevention nor do they have the expertise to support program implementation (e.g., determining the cost and financing for the intervention, training instructors, and monitoring fidelity of intervention delivery). In addition, most CDC‐compiled interventions do not provide an implementation plan with details on program installation, instructor training requirements, class conduct, or program fidelity and adaptation.…”
Section: Challengesmentioning
confidence: 99%
“…The study with American seniors showed that they become aware in relation to the practice of preventing falls from the moment they realize the risk, that is, when they start to fall frequently (30) . However, the group of Brazilian seniors studied here may be considered in situation of greater vulnerability compared with the American seniors, as the Brazilians only recognized themselves as susceptible to falls and fractures upon reflection on risks and causes after the concreteness of fracture.…”
Section: Discussionmentioning
confidence: 99%